Structure Function Analysis of Temperature-Dependent Thermal Properties of Nm-Thin Nb2O5 - Lisa Mitterhuber; Elke Kraker; Stefan Defregger (Energies, 2019)
A 166-nm-thick amorphous Niobium pentoxide layer (Nb2O5) on a silicon substrate was investigated by using time domain thermoreflectance at ambient temperatures from 25 °C to 500 °C. In the time domain thermoreflectance measurements, thermal transients with a time resolution in (sub-)nanoseconds can be obtained by a pump-probe laser technique. The analysis of the thermal transient was carried out via the established analytical approach, but also by a numerical approach. The analytical approach showed a thermal diffusivity and thermal conductivity from 0.43 mm2/s to 0.74 mm2/s and from 1.0 W/mK to 2.3 W/mK, respectively to temperature. The used numerical approach was the structure function approach to map the measured heat path in terms of a RthCth-network. The structure function showed a decrease of Rth with increasing temperature according to the increasing thermal conductivity of Nb2O5. The combination of both approaches contributes to an in-depth thermal analysis of Nb2O5 film.